Isolation and Identification of Multidrug-Resistant Raoultella terrigena as a Causative Agent of Urinary Tract Infection in Pregnant Women in the South of Libya - Almthnany, Asma M.; Alsonosi, Abdlrhman M.; Elbreki, Mohamed F.; Alazraq, Aiyda M. (European Scientific Journal, ESJ, 2023)
Raoutella terrigena is an opportunistic bacteria that rarely cause infections in humans. It is facultative Gram negative, rod shaped, present mostly in water, plants, soil, fish and insects. Two strains of R. terrigena have been isolated during a study searching of the must causative bacteria of urinary tract infection, in pregnant women where it counted about 2% of the total isolates. Susceptibility test has revealed multi drug resistance to about 61.5 % of the used antibiotics. This is the first documented report of such infection in Libya.